Modified patient‐controlled remifentanil bolus delivery regimen for labour pain. (12th October 2012) - Jost, A.; Ban, B.; Kamenik, M.
Summary: To improve the analgesic efficiency and to simplify the administration of remifentanil for systemic analgesia in labour, we contrived a modified delivery regimen with a specific infusion profile and variable dosing and conducted a single‐blind randomised crossover study to compare it with the previous 'classical' regimen. Parturients received both regimens in interchangeable sets, each with five contractions. We compared pain and satisfaction scores, maternal and fetal vital parameters, side‐effects and other events. Twenty‐three parturients completed the study. No differences in observed parameters were noticed except for slightly lower blood pressure with the modified regimen. Pain estimates were lower in women starting with the modified regimen (p = 0.005), and there were fewer requests for analgesia within the lockout period (31 vs 69, p = 0.041) and bolus adjustments (0 vs 25, p < 0.001) with the modified regimen.